(untitled) (The Pakistan Development Review, 2012)
Williamson (2002) points out that ‘the world has seen two globalisation booms over the past two centuries and one bust. The first global century ended with World War I and the second started at the end of World War II, while the years in between were ones of anti-global backlash’. In the first period of globalisation, poverty fell from 84 percent in 1820 to 66 percent in 1910. In the second period of globalisation poverty fell from 55 percent in 1950 to 24 percent in 1992. In the inter-war period, the world population living in poverty remains probably stagnant. The historical negative relationship between globalisation and poverty masks variations within and between countries in their experiences with globalisation. Many decades of increasing globalisation have not yet silenced the debate over the benefits of globalisation. The fierce street protests surrounding the ministerial meeting of the WTO and similar protests at the World Bank and the IMF show that anti-globalisation debate is getting strong.